Effect of crown to implant ratio and implantoplasty on the fracture resistance of narrow dental implants with marginal bone loss: an in vitro study - Leitão-Almeida, Bruno (2021)
Background: Peri-implantitis is a biological complication that affects soft and hard tissues around dental implants. Implantoplasty (IP) polishes the exposed implant surface, to decontaminate it and make it less prone to bacterial colonization. This study investigates whether a higher clinical crown-to-implant-ratio (CIR) reduces implant fracture resistance and whether implants are more fracture-prone after IP in the presence of 50% of bone loss. Methods: Forty-eight narrow platform (3.5 mm) 15 mm long titanium dental implants with a rough surface and hexagonal external connection were placed in standardized bone-like resin casts leaving 7.5 mm exposed. Half were selected for IP. The IP and control groups were each divided into 3 subgroups with different clinical CIRs (2:1, 2.5:1 and 3:1). The implant wall width measurements were calculated using the software ImageJ v.1.51 through the analysis of plain x-ray examination of all the samples using standardized mounts. A fracture test was performed and scanning electron microscopy was used to evaluate maximum compression force (Fmax) and implant fractures. Results: IP significantly reduced the implant wall width (P < 0.001) in all reference points of each subgroup. Fmax was significantly higher in the 2:1 subgroup (control = 1276.16 N ± 169.75; IP = 1211.70 N ± 281.64) compared with the 2.5:1 (control = 815.22 N ± 185.58, P < 0.001; IP = 621.68 N ± 186.28, P < 0.001) and the 3:1 subgroup (control = 606.55 N ± 111.48, P < 0.001; IP = 465.95 N ± 68.57, P < 0.001). Only the 2.5:1 subgroup showed a significant reduction (P = 0.037) of the Fmax between the controls and the IP implants. Most fractures were located in the platform area. Only 5 implants with IP of the 2:1 CIR subgroup had a different fracture location (4 fractures in the implant body and 1 in the prosthetic screw). Conclusions: IP significantly reduces the fracture resistance of implants with a 2.5:1 CIR. The results also suggest that the CIR seems to be a more relevant variable when considering the resistance to fracture of implants, since significant reductions were observed when unfavorable CIR subgroups (2.5:1 and 3:1 CIR) were compared with the 2:1 CIR samples.